Quantitative detection of Staphylococcus aureus, Streptococcus pneumoniae and Haemophilus influenzae in patients with new influenza A (H1N1)/2009 and influenza A/2010 virus infection - Safaeyan, Firouzeh; Nahaei, Mohammad Reza; Seifi, Sirus Jedary; Kafil, Hossein Samadi; Sadeghi, Javid (German Medical Science GMS Publishing House, 2015)
Introduction: Viral influenza is a seasonal infection associated with significant morbidity and mortality. In the United States more than 35,000 deaths and 200,000 hospitalizations are recorded annually due to influenza. Secondary bacterial infections or co-infections associated with cases of influenza are a leading cause of severe morbidity and mortality, especially among high-risk groups such as the elderly and young children. Aim: The aim of the present study was the quantitative detection of and in a group of patients with seasonal influenza A, influenza A () pandemic 2009, and patients with symptoms of respiratory infection, but the negative for serving as control group.Method: In total, 625 patients suspected respiratory infection from April 2009 to April 2010 were studied. There were 58 patients with influenza A and 567 patients negative for influenza A . From November 2010 to February 2011, 158 patients with respiratory symptoms were analyzed for seasonal influenza A. There were 25 patients with seasonal influenza A. To check the colonization status among the healthy individuals 62 healthy persons were further investigated. Individual were screened in parallel. The choices of special genes were amplified from clinical specimens using real-time PCR with a cutoff of 10 CFU/mL to differentiate colonization from infection in respiratory tract.Results: and were detected in 12%, 26% and 33% of patients with , while the corresponding figures were 9%, 19%, and 31% for negative patients. Among patients with seasonal influenza A 12% 24% , and 32% co-infections were detected, while influenza negative control group yielded 5% , 11% , and 10% , respectively. Conclusion: The results of this study indicated that the serotype of pandemic 2009 did not increase incidence of secondary infection with and . Quantitative detection of secondary bacterial infection by QR-PCR can help us for distinguishing colonization from infection and controlling misuse of antibiotics and bacterial drug resistances.